PENGEMBANGAN MEDIA PEMBELAJARAN KANJI LEVEL MENENGAH BERBASIS MEDIA SOSIAL INSTAGRAM - Yohani, Adisthi Martha; Nasution, Yenny Aristia; Dini Budiani; Nana Rahayu (PRASI, 2024)
Kanji learning is difficult if the teaching medium used is not interesting and relevant to technological advances. This research aims to describe the stages in developing middle-level Kanji teaching media with the help of Instagram social media to increase students' interest in learning middle-level Kanji. The research subjects were students studying Kanji in the third semester of the Japanese Language Education Study Program at FKIP, Riau University. The method used in this development research is the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. In this research, development was only carried out until the teaching media design stage. Teaching materials for 45 intermediate-level kanji were uploaded to an Instagram account. Each post contains one kanji accompanied by a mnemonic illustration, the meaning of the kanji, how to read onyomi, how to read kunyomi, a video of the writing sequence, and is equipped with examples of vocabulary and the application of the kanji in simple sentences. The results of the development of teaching media in this research were: 1) analysis found that the average score of students was low because the teaching media was less interesting and difficult to remember. 2) produce an Instagram-based teaching media design containing illustrations and video tutorials related to Kanji teaching with interesting visualizations. The conclusion of the research is that the presence of interesting visual-based teaching media and the help of social media such as Instagram are needed to increase understanding of intermediate-level Kanji teaching material. Keywords: Kanji, intermediate level, teaching media, Instagram, development.   Abstrak Pembelajaran Kanji sulit dilakukan jika media ajar yang digunakan kurang menarik dan relevan dengan kemajuan teknologi. Penelitian ini bertujuan untuk mendeskripsikan tahap-tahap dalam pengembangan media ajar Kanji level menengah berbantuan media sosial Instagram untuk meningkatkan minat peserta didik dalam pembelajaran Kanji level menengah. Subjek penelitian adalah peserta didik yang menempuh pembelajaran Kanji di semester tiga Program Studi Pendidikan Bahasa Jepang di FKIP Universitas Riau. Metode yang digunakan pada penelitian pengembangan ini adalah model ADDIE yang terdiri dari lima tahapan yaitu analisis (analyze), desain (design), pengembangan (develop), implementasi (implement) dan evaluasi (evaluate). Pada penelitian ini pengembangan baru dilaksanakan hingga tahap desain media ajar. Materi ajar sebanyak 45 Kanji level menengah diunggah ke sebuah akun Instagram. Setiap post memuat satu Kanji dilengkapi dengan ilustrasi mnemonik, makna Kanji, cara baca on’yomi, cara baca kunyomi, video urutan penulisan serta dilengkapi dengan contoh kosakata dan penerapan Kanji tersebut dalam kalimat sederhana. Hasil dari pengembangan media ajar pada penelitian ini adalah 1) ditemukannya analisis bahwa nilai rata-rata peserta didik rendah karena media ajar yang kurang menarik hingga sulit diingat. 2) dihasilkannya desain media ajar berbasis Instagram yang berisi ilustrasi dan video tutorial terkait pengajaran Kanji yang visualisasinya menarik. Simpulan dari penelitian adalah bahwa diperlukan kehadiran media ajar berbasis visual menarik serta bantuan media sosial seperti Instagram untuk meningkatkan pemahaman dengan terhadap materi ajar Kanji level menengah.